Highly furosemide uptake employing magnetic graphene oxide: DFT modeling combined to experimental approach (2023)
Furosemide (FUR) is a diuretic employed in hypertension treatment, this drug is excreted in unchanged form by human body which contributes to water contamination and toxic effects for humans and the environment. Due to the ineffective removal of this pollutant by conventional water treatment methods, this work reports a synthesis of magnetic graphene oxide (GO‧Fe3O4) with different amounts of iron nanoparticles for FUR adsorption. The nanomaterials were characterized by FTIR, XRD, SEM, Raman, and VSM techniques. DFT modeling and thermodynamic parameters show that the FUR adsorption is exothermic, favorable, and predominantly occurs in chemical interactions. The experimental study demonstrated that the best adsorbent was GO‧Fe3O4 1:1 showing a removal percentage and adsorption capacity of 96.15% and 96.91 mg g−1, respectively, at pH 3.0 and 293.15 K. The process was dependent on initial concentration, adsorbent dosage, and pH. ionic strength doesn’t significantly affect the adsorbent performance of GO‧Fe3O4 1:1. Sips and PSO model presented the best adjustment for experimental data, suggesting that the process occurs in a heterogeneous surface. Finally, GO‧Fe3O4 1:1 exhibited a high removal percentage after several cycles of adsorption/desorption.